The Potential Development of Karang Tawulan Beach as a Tourism Destination in Tasikmalaya Regency - Hubertina Karolina Ngarbingan; Nihan Lanisy; Anisa Zahwa (International Journal of Applied Business and International Management, 2023)
ABSTRACTÂ As a maritime country, Indonesia has great potential to develop marine tourism. Biodiversity and socio-cultural diversity are unique and attractive to domestic and foreign tourists. Tasikmalaya is one of the regencies in West Java Province, which has several tourist attractions on the south coast, which are very beautiful and unspoiled. Known as one of the marine tourism in Tasikmalaya, Karang Tawulan Beach is one of the tourist destinations that has the potential to develop. However, the potential that exists has not been explored yet by the local government. Based on the condition of Karang Tawulan beach, the attractions, supporting facilities, and infrastructures require innovation by settled development planning, consistent implementation, and measurable and constructive evaluation. Therefore, this research aims to determine the potential that can be developed in Karang Tawulan Beach as a tourist destination in Tasikmalaya. This potential is categorized based on Cooper's theory (2000) including aspects of 4A, namely attractions, accessibility, amenities, and ancillary that are benchmarks for the development of a tourism destination. The research method used is descriptive qualitative. Data collection techniques used were interviews (in-depth interviews), observation, and triangulation. The data analysis method used is SWOT (Strength, Weakness, Opportunities, Thread) and AHP (Analytical Hierarchy Process).Â Keywords: SWOT, Sustainable TourismAnalytical Hierarchy Process.